The sensitivity and specificity of thyroglobulin concentration using repeated measures of urinary iodine excretion - Ma, Zheng F.; Venn, Bernard J.; Manning, Patrick J.; Cameron, Claire M.; Skeaff, Sheila A. (European journal of nutrition, 2018)
Purpose Iodine deficiency affects 30% of populations worldwide. The amount of thyroglobulin (Tg) in blood increases in iodine deficiency and also in iodine excess. Tg is considered as a sensitive index of iodine status in groups of children and adults, but its usefulness for individuals is unknown. The aim of this study was to determine the diagnostic performance of Tg as an index of iodine status in individual adults. Methods Adults aged 18–40 years ( n = 151) provided five spot urine samples for the measurement of urinary iodine concentration expressed as μg/L (UIC), μg/g of creatinine (I:Cre), and μg/day (estimated UIE); the mean of the five samples was used as the reference standard. Participants also provided a blood sample for the determination of Tg, thyroid-stimulating hormone (TSH), and free thyroxine (FT4). Results The median of UIC, I:Cre, estimated UIE, and Tg was 72 (range 16–350) μg/L, 90 (range 33–371) μg/g, 129 (range 41–646) μg/day, and 16.4 (range 0.8–178.9) μg/L, respectively. Using Tg cut-offs of >10, >11, >13, and >15 μg/L, the sensitivity and specificity for UIC, I:Cre, and estimated UIE ranged from 52 to 79% and 20–48%, respectively, below the acceptable value of ≥80%. Furthermore, receiver-operating characteristic (ROC) curves for Tg using the three measurements of urinary iodine were situated close to the chance line and the area under the curve ranged from 0.49 to 0.52. Conclusions The results from this cross-sectional study indicate that Tg has low sensitivity and specificity to repeated measures of urinary iodine excretion. Further studies are still needed to investigate the usefulness of Tg as a biomarker of individual iodine status.